Crisis Leadership Styles - Bligh Versus Gillard: A Content Analysis of Twitter Posts on the Queensland Floods - De Bussy, Nigel; Paterson, Ann (John Wiley & Sons, Ltd., 2012)
This paper presents a quantitative and qualitative content analysis of Twitter posts mentioning Queensland Premier Anna Bligh and Australian Prime Minister Julia Gillard during the 2011 Queensland flood crisis. The contrast in the perceived styles of the two leaders is analysed using the theory of transformational leadership as a framework. The implications for effective leadership communication in a crisis are discussed, notably, strategies for instilling pride and gaining respect and trust. The study also highlights the emerging role of Twitter in setting the media agenda at times of fast-breaking news.